Vitamin C und Thiamin im Septischen Schock: eine retrospektive Vorher-Nachher-Studie an chirurgischen Patienten = Vitamin C and thiamine in septic shock : a retrospective before-and-after study on surgical patients - Dietrich, Maximilian; Märtens, Malte; Forst, Maik von der; Bruckner, Thomas; Uhle, Florian; Fiedler-Kalenka, Mascha; Weiterer, Sebastian; Hackert, Thilo; Brenner, Thorsten; Weigand, Markus A. (Anästhesiologie & Intensivmedizin, 2021)
Background: The administration of vitamin C and thiamine in septic shock is an innovative therapeutic approach. This study investigated the effect of vitamin C and thiamine in a surgical patient cohort with a predominantly abdominal focus. Methods: Clinical care data of septic shock patients between November 2017 and December 2019 were analysed retrospectively. All patients received sepsis therapy including hydrocortisone. The adjunctive therapy with 1.5 g vitamin C every 6 hours and 200 mg thiamine every 12 hours over 4 days was introduced in January 2019. The control group consisted of patients treated before the introduction of adjunctive therapy. Primary endpoints were in-hospital and 28-day mortality. Secondary endpoints were the duration of the patients' intensive care and invasive ventilation as well as SOFA score, C-reactive protein (CRP), serum creatinine, procalcitonin and leukocytes. Results: Both groups included 61 patients. The abdomen was the most frequent infection site (80 %). 22 patients (36.1 %) of the vitamin group and 27 patients (44.3 %) of the control group had died after 28 days (p = 0.356). In-hospital mortality of the vitamin group was 41.0 %, compared with 54.0% in the control group (p = 0.147). The duration of mechanical ventilation (6 days vs. 10 days, p = 0.029) was significantly shorter in the vitamin group. There were no significant differences in creatinine or the need for renal replacement therapy. Conclusion: High-dose vitamin C and thiamine in septic shock did not significantly reduce 28-day or in-hospital mortality in this analysis. However, a shorter duration of mechanical ventilation without an increased rate of renal complications was observed.